Autologous lipoaspirate as a new treatment of vulvar lichen sclerosus: A review on literature - Sluis, Nanouk; Scheers, Esther C.A.H.; Krenning, Guido; Lei, Berend; Oonk, Maaike H.M.; Dongen, Joris A. (Experimental dermatology, 2022)
Lichen sclerosus (LS) is a chronic inflammatory dermatosis that mostly affects the genital and anal skin areas. Symptoms may vary from pruritis and pain to sexual dysfunction; however, LS can also be asymptomatic. LS occurs at all ages and in both sexes. Approximately 5% of all women affected by vulvar LS will develop vulvar squamous cell carcinoma. Topical treatment is safe but less effective resulting in chronic course in most patients, who suffer from persistent itching and pain. In severe cases of therapy‐resistant LS, there is no adequate treatment. Fat grafting is a novel regenerative therapy to reduce dermal fibrosis. The therapeutic effect of adipose tissue grafts for LS is already investigated in various pioneering studies. This review provides an overview of these studies and the putative mechanisms‐of‐action of fat grafting to treat LS.